Herbicide Residues in Manure, Compost, or Hay - Jason A. Ferrell; Petere J. Dittmar; Brent A. Sellers; Pratap Devkota (EDIS)
When purchasing compost, it is important to understand that some manure-based products can contain herbicide residues that can affect the growth of certain plants. Manure from animals that have been fed forage treated with aminopyralid or other closely related herbicides, such as clopyralid or picloram, can be contaminated with these herbicides, which severely restrict the growth of legume and solanaceous crops and other broadleaf plants. This 3-page fact sheet discusses aminopyralid, compost, questions to ask when purchasing bulk compost or mulch, conducting a bioassay, aminopyralid injury symptoms, and steps to consider if contaminated manure or compost has been added to a garden or field site.